Biological Study for Leishmaniasis Cutaneous In Thi-Qar Governorate: Studi Biologis untuk Leishmaniasis Kutaneus di Kegubernuran Thi-Qar - Dakhil, Athraa Shakir (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Cutaneous leishmaniasis (CL), a parasitic disease transmitted by sandflies, remains a pressing public health issue in endemic regions. Specific Background: In Iraq, particularly within Dhi-Qar Governorate, CL has shown persistent prevalence, yet comprehensive long-term surveillance is limited. Knowledge Gap: Despite various clinical and diagnostic advancements, there is a lack of regional data analyzing demographic, geographic, and seasonal trends in CL incidence over an extended period. Aims: This study aims to monitor and evaluate the epidemiological patterns of CL in Dhi-Qar from 2020 to 2024 using hospital surveillance data. Results: A total of 3,882 cases were recorded, with a higher prevalence among males (53.16%) and rural residents (52.53%). Children aged 5–15 were the most affected group (41.6%). Infections peaked during winter (40.7%) and were most frequent on lower limbs (43.35%). Novelty: This research represents one of the few longitudinal studies in Iraq detailing the spatial, temporal, and anatomical distribution of CL at the governorate level. Implications: The findings provide critical insights for targeted public health interventions and underscore the need for improved awareness, especially in rural areas, to control disease spread and reduce long-term health impacts.Highlight : Infection rates were higher among males (53.16%) and in rural areas (52.53%). Children aged 5–15 years had the highest infection rate (41.6%) over the 4-year period. Winter season showed the highest number of cases (40.7%), indicating a seasonal pattern of transmission. Keywords : Cutaneous Leishmaniasis, Dhi-Qar Governorate, Epidemiology, Seasonal Variation, Public Health